World development report 1978-2005 with selected World development indicators 2004 - World Bank. (Washington, D.C. World Bank, 2005)
Includes the text of all 25 previous editions of The World Development Report from 1978 to 2003, as well as pdf versions of the 2002 and 2003 editions.
System requirements: Hardware: IBM-compatible PC (will not work on Macintosh systems) ; Intel Pentium 11 or compatible processor, 300 MHz or higher; 64 MB of RAM minimum, Screen resolution 800x600 pixels minimum; pointing device (mouse). Software: Adobe Acrobat versions 4 or 5; Microsoft Office 97 or above; Excel 2000 - this is the minimal configuration needed for macro-calaculation. Some problems may occur on an Excel 97 configuration.
Keywords: International economic relations; International economic integration; Economic indicators